2021
DOI: 10.18632/aging.203256
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment neutrophil-to-lymphocyte ratio predicts the benefit of gastric cancer patients with systemic therapy

Abstract: Pretreatment neutrophil-to-lymphocyte ratio (NLR) has been reported to be associated with the prognosis of inoperable gastric cancer patients with systemic therapy. However, no consensus on the association has been reached. In this study, we mainly evaluated whether pretreatment NLR predicted the benefit of inoperable gastric cancer patients with systemic therapy, including chemotherapy, targeted therapy and immunotherapy. PubMed, Embase and Cochrane Library databases were systematically searched from inceptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…The advantage of CXI over Fearon’s criteria is that it includes NLR and serum albumin. Furthermore, previous studies demonstrated that NLR and serum albumin had significant associations with the prognosis in patients with GC [ 32 , 33 , 34 ], which might account for why low CXI, instead of cachexia diagnosed by Fearon’s criteria, was significantly associated with worse OS in this study.…”
Section: Discussionmentioning
confidence: 54%
“…The advantage of CXI over Fearon’s criteria is that it includes NLR and serum albumin. Furthermore, previous studies demonstrated that NLR and serum albumin had significant associations with the prognosis in patients with GC [ 32 , 33 , 34 ], which might account for why low CXI, instead of cachexia diagnosed by Fearon’s criteria, was significantly associated with worse OS in this study.…”
Section: Discussionmentioning
confidence: 54%
“…The neutrophils, lymphocytes, platelets, monocytes and C-reactive protein are all common inflammatory biomarkers and a great number of studies have revealed the prognostic role of NLR, PLR, LMR and GPS in tumors. Several met-analyses demonstrated that elevated pretreatment NLR was a prognostic risk factor in colorectal cancer (HR = 1.57, 95%CI: 1.39-1.78, P < 0.001)[ 36 ], gastric cancer (HR = 1.78, 95%CI: 1.59-1.99, P < 0.001)[ 37 ], laryngeal cancer (HR = 1.76, 95%CI: 1.53-2.03, P < 0.001)[ 38 ] and non-small cell lung cancer patients (HR = 2.86, 95%CI: 2.11-3.87, P < 0.001)[ 39 ]. Furthermore, the prognostic value of GPS has been verified in ovarian cancer (HR = 1.62, 95%CI: 1.38-1.91, P < 0.001), esophageal squamous cell cancer (HR = 1.66, 95%CI: 1.14-2.41, P = 0.008), colorectal cancer (HR = 2.20, 95%CI: 1.88-2.57, P < 0.001) and lung cancer patients (HR = 2.058, 95%CI: 1.51-2.80, P < 0.05) by several meta-analyses[ 14 , 40 - 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Low ALC and high AMC have been reported as prognostic factors for OS and disease-free survival (DFS) in resectable stomach cancer, with cutoff values of 1734/µL and 1720/µL, and 672.4/µL and 510/µL, respectively [ 17 , 18 ]. The prognostic significance of NLR, LMR, and PLR in stomach cancer has been reported in several meta-analyses ( Table 6 ) [ 13 , 19 , 20 , 21 , 22 ]. Although the target population and cutoff values of each study were widely heterogeneous, an increase in NLR and PLR and a decrease in LMR were associated with a worse prognosis.…”
Section: Discussionmentioning
confidence: 99%